HUBUNGAN PARITAS DAN RIWAYAT SC DENGAN KEJADIAN PLACENTA PREVIA DI RSUD ARIFIN ACHMAD PEKANBARU - Anita, Wan (Jurnal Endurance, 2017)
The Causes of maternal mortality rate (MMR) major was bleeding, bleeding that common in pregnant women one of which was placenta previa. Placenta previa is abnormal placental location, that is the lower uterine segment that partially or completely cover the opening of the birth canal. The purpose of this study to determine the relationship of parity and history of sectio cesarea (SC) with placenta previa in women giving birth at the Camar room I Arifin Achmad Pekanbaru. The design of this research was quantitative analytical with cross sectional approach. Samples were mothers who have placenta previa in 2013 which amounted to 135 cases. The sampling technique was total sampling. The analysis analysis using chi square test. The results showed respondents with parity 1 and> 3 amounted to 76 (56.3%) and the 2-3 parity totaled 59 people (43.7%). The history of SC in this study was the majority do not have a history of SC representing 84 people (62.2%) and history of SC amounted to 51 people (37.8%). This research obtained the results that respondents with placenta previa amounted to 91 (67.4%), and low-lying placenta amounted to 44 (32.6%). There is a relationship of parity 1 and> 3 on the incidence of placenta previa (p value = 0.034) and there is no history of SC relationship with the incidence of placenta previa (p value = 0.052). From the research results could be recommended to decrease the incidence of placenta previa is expected to health workers to provide information about the importance of planning a safe pregnancy and pregnant women for always to check the development of their pregnancy.Penyebab angka kematian ibu (AKI) yang utama adalah perdarahan, dimana perdarahan yang sering terjadi pada ibu hamil salah satunya adalah plasenta previa. Tujuan penelitian ini untuk mengetahui hubungan paritas dan riwayat sectio cesarea (SC) dengan kejadian plasenta previa pada ibu bersalin di ruang Camar I RSUD Arifin Achmad Pekanbaru. Desain penelitian adalah analitik kuantitatif dengan pendekatan cross sectional. Sampel adalah Â ibu bersalin yang mengalami plasenta previa tahun 2013 yang berjumlah 135 kasus. Teknik pengambilan sampel ini total sampling, dengan uji chi square. Hasil penelitian menunjukkan responden yang mempunyai paritas 1 dan > dari 3 berjumlah 76 orang (56,3%) dan paritas 2-3 berjumlah 59 orang (43,7%). Riwayat SC pada penelitian ini mayoritas tidak mempunyai riwayat SC berjumlah 84 orang (62,2%) dan ada riwayat SC berjumlah 51 orang (37,8%). Penelitian ini mendapatkan hasil bahwa responden dengan placenta previa berjumlah 91 orang (67,4%), dan placenta letak rendah berjumlah 44 orang (32,6%). Terdapat hubungan paritas 1 dan >3 terhadap kejadian placenta previa (p value = 0,034) dan tidak terdapat hubungan ada riwayat SC dengan kejadian placenta previa (p value = 0,052). Kepada petugas kesehatan untuk memberikan informasi tentang pentingnya merencanakan kehamilan dan Â selalu memeriksakan kehamilannya.